The relationship between impostor phenomenon and career decision-making difficulties among nursing interns: the mediating role of psychological resilience - He, Meina; Li, Yao; Hu, Hui; Yu, Zuqiang; Cai, Cong; Cheng, Yao; Ma, Lu; Liu, Shanshan (Frontiers in Psychology, 2024)
Background: In the face of a global nursing shortage, nursing interns are crucial to sustaining the healthcare workforce. However, these interns encounter significant challenges in career decision-making, often exacerbated by the impostor phenomenon, which impedes their capacity to make informed choices. Despite its importance, little research has been reported on the specific conditions and contributing factors that affect nursing interns' career decision-making processes. Objective: To understand the current status of nursing interns' impostor phenomenon, psychological resilience, and career decision-making difficulties, and to validate the mediating role of psychological resilience between impostor phenomenon and career decision-making difficulties using structural equation modeling. Methods: 582 nursing interns from four tertiary hospitals in Wuhan City, Hubei Province of China were selected by stratified random sampling. Data were collected with the Clance Impostor Phenomenon Scale, Career Decision-Making Difficulties Questionnaire, and the 10-item Connor–Davidson Resilience Scale through an online survey. Mediation effect tests were conducted using SPSS 26.0 and PROCESS software. Results: (1) The score for career decision-making difficulties was 99.34 (SD = 21.78), the score for impostor phenomenon was 57.58 (SD = 12.13), and the score of psychological resilience was 32.11 (SD = 8.50); (2) Psychological resilience had a significant negative correlation with career decision-making difficulties (r = −0.724, p < 0.01),and impostor phenomenon had a significant negative correlation with psychological resilience (r = −0.608, p < 0.01), and had a significant positive correlation with career decision-making difficulties (r = 0.700, p < 0.01).Psychological resilience played a partial mediating role between impostor phenomenon and career decision-making difficulties (p  <  0.01), with the mediating effect (Effect Value  =  0.518, Bootstrap 95% CI: 0.430, 0.610) accounting for 41.27% of the total effect. Conclusion: Career decision-making difficulties are common among nursing interns. Effective strategies should address the impostor phenomenon and promote psychological resilience to enhance self-awareness and create a supportive environment.